2006
DOI: 10.1017/ecp200694
|View full text |Cite
|
Sign up to set email alerts
|

A field study on hoof deceleration at impact in Standardbred trotters at various speeds

Abstract: Impact-related peak decelerations with high loading rates are described as indicators of mechanical stress to the limb. The hoof deceleration pattern in the beginning of the stance phase has recently been described, together with ground reaction force measurements at slow speed; however, no information is available at high speeds. The objective of the present study was to investigate the hoof deceleration pattern following impact at slow speeds, comparable to earlier force plate studies, and at high speeds on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 22 publications
1
22
0
2
Order By: Relevance
“…The absence of a significant difference in fqMax between walk and trot may be because the material properties of the foot and surface were constant between gaits, and frequency is highly influenced by material properties. Similar frequencies across a range of trotting speeds has been reported previously and an ex vivo study found a decrease of ~50 Hz between hoof‐impacts occurring at 0.75 and 1.25 m/s , similar to the nonsignificant differences reported in our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The absence of a significant difference in fqMax between walk and trot may be because the material properties of the foot and surface were constant between gaits, and frequency is highly influenced by material properties. Similar frequencies across a range of trotting speeds has been reported previously and an ex vivo study found a decrease of ~50 Hz between hoof‐impacts occurring at 0.75 and 1.25 m/s , similar to the nonsignificant differences reported in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Like others who have utilised hoof‐mounted accelerometers, we have reported high levels of within horse variation regarding vibration parameters . In order to minimise the within horse variation, the accelerometer was not removed between trials in this study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The power density spectrum of the z accelerometric signal (during the hoof braking phase) was calculated for each stride using a Fast Fourier Transform (Gustås et al, 2006b). The spectral density curves were then integrated for several frequency ranges (0-200, 200-400, 400-600, 600-800, 800-1000 and 1000-2000 Hz) to give vibration energy values that could be compared between surfaces.…”
Section: Data Processingmentioning
confidence: 99%
“…This suggests that parameters that affect horizontal braking are important to the orthopaedic health of the horse. At different speeds, Gustas et al . (2006b) have documented that the absolute length of the hoof‐braking period is between 30 and 50 ms and is independent of speed.…”
Section: Introductionmentioning
confidence: 99%